A Comprehensive Exploration of Chemical Inventory: Multifaceted Challenges and Profound Insights - Ahmad Abdulkareem Al-Shaer; Mohammad S. Al-Ghafli (ExcelingTech, 2023)
This paper provides a comprehensive exploration of the multifaceted challenges and profound insights associated with chemical inventory. It highlights the critical findings and contributions in the areas of safety, efficiency, and compliance within chemical inventory facilities. By emphasizing the importance of robust risk assessments, implementation of safety measures, adherence to regulatory frameworks, and development of comprehensive emergency response plans, this paper aims to foster safer, more efficient, and compliant chemical inventory environments. Drawing attention to the tragic Beirut port explosion in 2020, this paper underscores the urgent need to address the challenges inherent in chemical inventory and presents valuable insights to mitigate potential hazards.